TESL PRACTICUM TEACHERS’ VIEWS ON THE ROLE OF GAMIFICATION IN ENHANCING STUDENT ENGAGEMENT - Hamzah, Izznur Hajar; Ramalingam, Sangeeth (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Gamification is increasingly recognized as a powerful tool in education for enhancing student engagement. While many studies explore its effects on learning, few focus on the perspectives of TESL practicum teachers in Malaysian secondary ESL classrooms. As novice educators begin integrating gamification, there is a limited understanding of their perceptions, implementation strategies, and the challenges they face. This study investigates the effectiveness of gamification in improving ESL student engagement and explores TESL practicum teachers’ views using a qualitative approach, involving two respondents who actively integrate gamification as a teaching tool in their classrooms. Guided by Behaviourism, Cognitive Load Theory, and Self-Determination Theory (SDT), the findings offer insights into how gamification can be effectively used in ESL teaching. The study addresses a key gap in the literature by highlighting practicum teachers’ real-world experiences and guides when and how to implement gamification in language classrooms. It also underscores the need for teacher training programs to better prepare future educators with practical, research-based gamification strategies. Future research should explore gamification’s long-term effects, its role in specific language skills, and how it can be sustained in ESL pedagogy.